Resilinesi pada Nasabah Korban Kasus Pencucian Uang di KSP X - sodiq, alwi mahardhika; Widjanarko, Mochamad; Suharsono, Suharsono (Universitas Al Azhar Indonesia, 2024)
This research aimed to find out about the psychological resilience of victims who experienced the loss of their savings due to a case of customer money laundering at one of the KSP X (saving and credit cooperative) in Kudus which had been declared bankrupt. Based on this research, social support is described as an external factor that influences the dynamics of victim resilience, and client self-efficacy is described as an internal factor. This research is a qualitative one with a phenomenological approach, and data sources were collected through purposive sampling. The data collection technique used is triangulation, data analysis is carried out inductively or qualitatively. Data collection was carried out through observation, interviews and documentation. The subjects in this research were three male customers who lost large amounts of their savings as a result of the money laundering case of KSP X which had been declared bankrupt. The results of this research show that customers have been able to achieve resilience, because they have the self-efficacy to get out of difficult times as victims of money laundering cases and get social support from their family and those closest to them so they can recover quickly. The painful events experienced by the customers were able to be overcome well, even though it took around three years to regulate their emotions. This painful incident taught customers something very meaningful during their lifetime, namely to always be careful in making decisions and giving authority or trust to other people.Keywords - Customers, Resilience, Self Efficacy.